Student’s perception regarding tutorials in pre-clinical undergraduate medical education (Journal of Fatima Jinnah Medical University, 2024)
Background: Tutorials are one of oldest teaching methodologies and are effectively being used for teaching in medical education. The objective of this study is to identify student’s perspective regarding conventional tutorial teaching in undergraduate, pre-clinical medical curriculum and recognise appropriate changes needed to improve learning of higher order critical thinking and decision making skills among medical graduates in tutorials.Subject and methods: This is a mixed method study conducted at Fatima Jinnah Medical University. Qualitative data was collected by structured interviews from twelve second year medical students. Interviews were transcribed and thematic analysis done for results. DREEM questionnaire was modified to design a questionnaire and was used to collected quantitative data from second year MBBS class, through an online survey.Results: Twelve female medical students of 2nd year MBBS of FJMU participated in structured interviews. Content analysis of transcribed interviews identified three main themes i. e self-directed learning, collaborative learning and problem-based learning. Majority of students made response that tutorials provide active class room participation (60%), learning motivation (55.7%) and learning stimulation (48%).  They also opined learning is learner centered (53%) and objective oriented (70%), it builds competence (50%) and confidence (67%), add value to time (57%) and enhances interpersonal skills (44%) in stress free environment (70%). Students also valued handouts and learning materials provided in tutorials (59.6%). However, they felt teaching in tutorials is monotonous (69.36%), do not support memorization (44%) and lack problem solving skills learning (39%).Conclusion: Overall, tutorial learning can be a powerful tool for enhancing student learning and development when implemented thoughtfully and strategically.
Keywords: Tutorials; perception; self-directed learning; collaborative learning; problem-oriented learning